DIABETES MELLITUS TIPO1: EVOLUÇÃO DA EFICÁCIA ADAPTATIVA E PSICOTERAPIA BREVE OPERACIONALIZADA - Bechara, Glaucia Margonari (2011)
The aim of this study was to evaluate the adaptive efficiency, before and after an intervention in Brief Psychotherapy Operational in a patient with Diabetes Mellitus type 1. The instruments used were the Preventive Clinical Interview, the Operational Adaptive Diagnostic Scale - EDAO and Brief Psychotherapy Operational - PBO. The design of this research was made by the clinical method combined with descriptive observational method. We conducted a case study of a patient diagnosed with Diabetes Mellitus type 1, who underwent eight diagnostic interviews to obtain the clinical diagnosis and then to twelve sessions of Brief Psychotherapy Operational. After six months of the end of the sessions the patient attended an interview for Follow up. The adaptive diagnosis, after the first interviews was: Adaptation Inefficacy, which were detected in situations-problems to be addressed in the PBO was organized and the planning of this intervention. After completion of the PBO and six months after the patient underwent an interview Follow up, in which the diagnostic classification was: Mild Inefficient Adaptation. We conclude that this case study an evolution in the adaptive diagnosis after the intervention in PBO, showing the importance of customer service in Brief Psychotherapy Operational.